The linkage between mercury-caused neuro- and genotoxicity via the inhibition of DNA repair machinery: fish brain model - Nedzvetsky, V.S.; Gasso, V.Y.; Herrmann, B.; Novitskiy, R.O. (Medicni Perspektivi, 2022)
Heavy metals in model conditions as well as industrial pollution launch disturbances in neural cells of different animals and human beings. The neurotoxicity of mercury, which is one of the most toxic heavy metals, has been studied for several decades. However, its low doses chronic exposure effects for neural tissue cells are still poorly understood. Therefore, the basic molecular mechanisms of mercury should be clarified. The purpose of our research is to clarify the mechanism of mercury genotoxicity, the role of the DNA repair protein apurinic/apyrimidinic endonuclease 1 (APE1) in neural tissue cells, and the response to inorganic mercury-induced neurotoxicity. In our model, we used juvenile rainbow trout exposed to mercury chloride with a range of doses 9‑36 µg/L for 60 days to study the cytotoxicity of chronic exposure. We detected the reactive oxygen species (ROS) production as an index of oxidative stress and APE1 as a marker of cellular DNA damage response in a neural cell. The ROS level was measured by using the fluorometric method based on 2’,7’-dichlorofluorescein diacetate reaction. The analyses of markers of the DNA repair (APE1) and apoptosis (B cell lymphoma-2 anti-apoptotic protein – Bcl-2) were carried out with western blotting. The mercury chloride chronic exposure induced statistically significant upregulation of the ROS production in the fish brain. Contrary, the mercury low doses stimulated the downregulation of APE1 expression in the brain tissue. Furthermore, mercury chronic exposure inhibited the expression of Bcl-2 in the animals treated with 18 and 36 µg/L mercury chloride. The harmful effect of mercury could be promoted by oxidative stress generation. The downregulation of APE1 expression could lead to a lack of DNA damage response efficacy and initiate the decline in neural cell functioning. Obtained data on the APE1 expression have shown that the neurotoxic effect of mercury could be mediated, at least partially, by the decline in cellular DNA damage response in the brain. The evaluation of decrease in DNA repair response via detection of the APE1 expression can be a prospective tool to reveal the deleterious effects of toxicants in terms of their neuro- and genotoxicity.